Classroom acoustics and cognition: A review of the effects of noise and reverberation on primary school children's attention and memory. Issue 3 (September 2022) - Mealings, Kiri
Classroom acoustic conditions are often suboptimal, so how do they affect children's cognition? This review synthesized research assessing the effect of different classroom acoustic conditions on children's attention and memory. A comprehensive search of four online databases was conducted in January 2022 using the search term classroom AND (noise* OR reverberat* OR acoustic*) AND (cognit* OR attention OR memory OR processing) . The results revealed 21 relevant papers plus an additional 10 from their references. The papers assessed the effect of a range of chronic and acute acoustic exposures on different attention and memory processes. Overall, the majority of studies showed a negative effect or no effect of higher noise levels, longer reverberation times, or lower speech clarity on children's cognition. It would therefore be beneficial to improve classroom acoustic conditions if possible. Suggestions for future research to more fully understand the effect of different classroom acoustic conditions on children's cognition are posed.